Do polypills lead to neglect of lifestyle risk factors? Findings from an individual participant data meta-analysis among 3140 patients at high risk of cardiovascular disease. (September 2016) - Selak, Vanessa; Bullen, Chris; Stepien, Sandrine; Arroll, Bruce; Bots, Michiel; Bramley, Dale; Cass, Alan; Grobbee, Diederick; Hillis, Graham S; Molanus, Barbara; Neal, Bruce; Patel, Anushka; et al.
Aim: The aim of this study was to investigate whether polypill-based care for the prevention of cardiovascular disease (CVD) is associated with a change in lifestyle risk factors when compared with usual care, among patients with CVD or high calculated cardiovascular risk. Methods: We conducted an individual participant data meta-analysis of three trials including patients from Australia, England, India, Ireland, the Netherlands and New Zealand that compared a strategy using a polypill containing aspirin, statin and antihypertensive therapy with usual care in patients with a prior CVD event or who were at high risk of their first event. Analyses investigated any differential effect on anthropometric measures and self-reported lifestyle behaviours. Results: Among 3140 patients (75% male, mean age 62 years and 76% with a prior CVD event) there was no difference in lifestyle risk factors in those randomised to polypill-based care compared with usual care over a median of 15 months, either across all participants combined, or in a range of subgroups. Furthermore, narrow confidence intervals (CIs) excluded any major effect; for example differences between the groups in body mass index was −0.1 (95% CI −0.2 to 0.1) kg/m 2, in weekly duration of moderate intensity physical activity was −2 (−26 to 23) minutes and the proportion of smokers was 16% vs 17% (RR 0.98, 0.84 to 1.15) at the end of trial. Discussion: This analysis allays concern that polypill-based care may lead to neglect of lifestyle risk factors, at least among high-risk patients. Maximally effective preventive approaches should address lifestyle factors alongside pharmaceutical interventions, as recommended by major international guidelines.